Kontribusi Lingkungan Sekolah Terhadap Pengembangan Social Emotional Learning (SEL) Anak Usia Dini di Sekolah RA I’Anatus Syibyan Blumbungan Pamekasan - Susilawati Susilawati; Sitti Romlah (Social Science Academic, 2026)
The development of Social-Emotional Learning (SEL) in early childhood is a crucial aspect of education, as it plays a vital role in shaping children's abilities to manage emotions, interact socially, and build character. This study aims to analyze the implementation of SEL, the school environment's contribution to SEL development, the outcomes of this development, and the supporting and inhibiting factors at RA I’Anatus Syibyan Blumbungan, Pamekasan. A qualitative approach was employed, utilizing data collection techniques such as observation, interviews, and documentation. The research subjects included the school principal, homeroom teachers, assistant teachers, and students aged 4–6 years. Data analysis involved data reduction, data presentation, and conclusion drawing. The results indicate that SEL is implemented through the cultivation of positive behavioral habits, play-based learning activities, teachers setting a good example, and a personal approach. The school environment contributes to SEL development through positive social interactions, a supportive school culture, and a physical environment that facilitates collaborative activities. SEL development has resulted in improved abilities among children to manage emotions, cooperate, show empathy, follow rules, and build self-confidence. Supporting factors include a conducive school environment, teachers serving as role models, adequate facilities and infrastructure, and parental support; conversely, inhibiting factors include excessive gadget use, diverse parenting styles, and limitations in educators' competence.